Elementary School Students’ Understanding of the Relationship Between Environmental, Social, and Economic Aspects Through Biology Education - Iksan, Muhamad; Acoci; Tarno; Farisatma (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
Elementary school students’ understanding of the interrelationship between environmental, social, and economic aspects serves as a crucial foundation for fostering early awareness of sustainability. This study aims to analyze the effect of a contextual-based biology education approach on improving students’ understanding across five key aspects: environmental understanding, social understanding, economic understanding, analytical ability of interconnection, and sustainability awareness. The research employed a quantitative method using a quasi-experimental design of the Nonequivalent Control Group Design type. The subjects consisted of 22 fifth-grade students divided into two groups: experimental and control. Instruments included tests, questionnaires, and observation sheets. Data were analyzed using normality tests, homogeneity tests, independent samples t-tests, linear regression, and multicollinearity tests. The results indicate that the contextual learning approach has a significant effect on all student understanding variables, with the majority of students in the experimental group achieving high scores, particularly in environmental understanding and sustainability awareness. The t-test showed a significant difference between the experimental and control groups, while the regression analysis revealed a positive relationship between variable X and all Y variables. These findings support the effectiveness of contextual approaches as a holistic learning strategy in elementary education.